The Prevalence of Antimicrobial-Resistant Escherichia coli in Two Species of Invasive Alien Mammals in Japan - MIYAZAKI, Kei; OGURA, Go; TAKASE, Kozo; NAKAYAMA, Ayano; TAMAKI, Masanobu; OBI, Takeshi; MIYAMOTO, Atsushi; SAKEMI, Yoko; OKA, Tatsuzo; NAKAMURA, Ichiro; KAWAMOTO, Yasuhiro (Journal of Veterinary Medical Science, 2011)
The prevalence of antimicrobial resistance in 128 Escherichia coli isolates was investigated in two species of invasive alien mammals (IAMs): the small Asian mongoose (SAM) and Japanese weasel (JW). The SAM is found on the main island of Okinawa, Japan, where a large number of livestock is available, and the JW is present on a small island, where is isolated from the main island, and have a small number of livestock. We focused on the two IAMs, inhabiting under the different environments, and compared their prevalence of antimicrobial-resistant E. coli. In the comparison of the frequencies of antimicrobial-resistant E. coli isolates between the SAM and JW, JW showed significantly higher prevalence of resistance against three drugs, ampicillin, chlortetracycline and nalidixic acid, compared with SAM's test results (P<0.05). The blaTEM gene and the aph1 gene were detected in 35 subjects (91%) of ampicillin-resistant isolates and 6 subjects (100%) of kanamycin-resistant isolates, respectively. The tet (A) gene was detected in 62 subjects (46%) of CTC-resistant isolates, and the tet (B) gene was detected in 25 subjects (8%) of those in IAM. The present results suggest that some IAMs were the carrier of antimicrobial-resistant bacteria and their genes, and the frequencies of these resistances were different between two IAM species.